Contactless actuation of perfluorinated ionomer membranes in salt solution: an experimental investigation - Boldini, Alain; Rosen, Maxwell; Cha, Youngsu; Porfiri, Maurizio (Nature Publishing Group, 2019)
A variety of modeling frameworks have been proposed for ionic polymer metal composites (IPMCs), but the physical underpinnings of their actuation remain elusive. A critical step toward the validation of existing theories and transition to engineering practice entails the design of new experimental paradigms that could support hypothesis-driven research. While several factors exacerbate the complexity of experimenting with IPMCs, the presence of the electrodes plays a major role by hindering the repeatability of the results and bringing a number of difficult-to-measure parameters into the picture. Here, we seek to address these experimental confounds by investigating contactless actuation of perfluorinated ionomer membranes in salt solution. In contrast to IPMCs that bend toward the anode in response to an applied voltage, ionomer membranes display a consistent deflection toward the cathode. Through hypothesis-driven experiments where the membrane width, solution concentration, and voltage applied across the electrodes are systematically varied, we elucidate electrochemistry and mechanics of contactless actuation. The applied voltage and solution concentration have a dominant role on the electrochemistry, while mechanics is mainly affected by the applied voltage and membrane width. Our results depict a complex scenario, which is expected to inform future theoretical inquiries about IPMC actuation.